2016
DOI: 10.1158/1078-0432.ccr-15-2624
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mithramycin Analogues with Improved Targeting of the EWS-FLI1 Transcription Factor

Abstract: Purpose The goal of this study was to identify second-generation mithramycin analogs that better target the EWS-FLI1 transcription factor for Ewing sarcoma. We previously established mithramycin as an EWS-FLI1 inhibitor, but the compound’s toxicity prevented its use at effective concentrations in patients. Experimental Design We screened a panel of mithralogs to establish their ability to inhibit EWS-FLI1 in Ewing sarcoma. We compared the IC50 to the maximum tolerated dose established in mice to determine th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 49 publications
2
51
0
Order By: Relevance
“…These findings provide a proof-of-concept for the targeting of the SOX2 transcriptional circuit in GBM. The recent development of mithramycin analogs with an improved toxicity profile (Osgood et al, 2016; Vizcaino et al, 2012) may provide the basis for testing this therapeutic strategy in clinical trials. Since we observed an upregulation of expression of genes that have pro-apoptotic functions or are implicated in antigen presentation, there is a strong rationale for future studies of the combination of mithramycin treatment with radiation therapy, chemotherapy (temozolomide) and/or immunotherapy in preclinical GBM models.…”
Section: Resultsmentioning
confidence: 99%
“…These findings provide a proof-of-concept for the targeting of the SOX2 transcriptional circuit in GBM. The recent development of mithramycin analogs with an improved toxicity profile (Osgood et al, 2016; Vizcaino et al, 2012) may provide the basis for testing this therapeutic strategy in clinical trials. Since we observed an upregulation of expression of genes that have pro-apoptotic functions or are implicated in antigen presentation, there is a strong rationale for future studies of the combination of mithramycin treatment with radiation therapy, chemotherapy (temozolomide) and/or immunotherapy in preclinical GBM models.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, mithramycin was well tolerated with the exception of the significant hepatic toxicity. Interestingly, the same effect was seen with trabectedin another compound linked to the suppression of EWS–FLI1 [18]. As is the case with mithramycin, the transaminitis associated with trabectedin is mitigated by pretreatment with dexamethasone [31].…”
Section: Discussionmentioning
confidence: 96%
“…However, a definitive answer to this question would aid in future development efforts for this class of compounds. Indeed, these data would help guide the selection of second-generation mithramycin analogs that offer the hope of therapeutic suppression of EWS–FLI1 based on an improved toxicity profile [18]. …”
Section: Discussionmentioning
confidence: 99%
“…In this report, we sought to determine if SWI/SNF dysregulation was a molecular feature contributing to the heightened sensitivity of tumors to mithramycin. We analyzed two independently generated datasets and found that cell lines with mutated or dysregulated SWI/SNF were indeed particularly sensitive to mithramycin and EC8042 (15). Using rhabdoid tumor as a model of dysregulated SWI/SNF, we show that mithramycin directly targets SWI/SNF by evicting the complex from chromatin.…”
Section: Introductionmentioning
confidence: 95%